2016
DOI: 10.1111/tra.12396
|View full text |Cite
|
Sign up to set email alerts
|

Ligation of FcγR Alters Phagosomal Processing of Protein via Augmentation of NADPH Oxidase Activity

Abstract: Proteolysis and the reduction of disulfides, both major components of protein degradation, are profoundly influenced by phagosomal redox conditions in macrophages. We evaluated the activation of phagocytic receptors that are known to influence activation of the phagocyte NADPH oxidase (NOX2), and its effect on phagosomal protein degrada- Phagocytosis is necessary for the destruction of pathogens, the clearance of cellular debris and the processing of exogenous protein antigen. While the hydrolysis of phagocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Recent data imply that distinct pathways regulate uptake kinetics of different particles as well as phagosome functions in macrophages, and these are further controlled by macrophage activation. It was demonstrated that both the phagocytic receptors (Dill et al , ; Balce et al , ) and pro‐inflammatory (Yates et al , ; Trost et al , ; Ghigo et al , ) and anti‐inflammatory activation (Varin et al , ; Balce et al , ) of macrophages affect phagosome functions and these are regulated by signalling pathways such as kinases (Hartlova et al , ) and E3 ligases (O. Bilkei‐Gorzo, T. Heunis, A. Härtlova, M. Trost, unpublished data ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data imply that distinct pathways regulate uptake kinetics of different particles as well as phagosome functions in macrophages, and these are further controlled by macrophage activation. It was demonstrated that both the phagocytic receptors (Dill et al , ; Balce et al , ) and pro‐inflammatory (Yates et al , ; Trost et al , ; Ghigo et al , ) and anti‐inflammatory activation (Varin et al , ; Balce et al , ) of macrophages affect phagosome functions and these are regulated by signalling pathways such as kinases (Hartlova et al , ) and E3 ligases (O. Bilkei‐Gorzo, T. Heunis, A. Härtlova, M. Trost, unpublished data ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, upregulation of baseline TLR2 and TLR8 expression by IFNγ, as shown herein, could promote more opportunities for ligation of released spirochetal PAMPs (33, 53) and TLR signaling itself may lead to a more rapid maturation of the phagosome (68). Alternatively, as shown by Balce et al (69) FcγR-mediated phagocytosis in association with IFNγ could facilitate phagosomal processing of proteins. IFNγ stabilizes MyD88 (70), in addition to modulation of the FcγR signaling cascade (59, 71), helping to enhance the recognition response to Tp .…”
Section: Discussionmentioning
confidence: 95%
“…In addition, alloantibody-FcγR I/FcγR III-dependent ROS production in macrophages is an important mediator of humoral immune damage during liver graft rejection (27). Opsonization of IgG on IFN-γ-activated macrophages led to diminished phagosomal processing of proteins in a PKC/Syk-NOX2dependent manner, which occurs at the level of the individual phagosome (28). Altered IgG subtype distribution and the resulting increase in IFN-γ production are observed in both patients with CGD and a CGD mouse model (29), indicating a possible feedback loop involving IFN-γ, IgG, FcγRs, and NOX2.…”
Section: Ros In Antigen Presentationmentioning
confidence: 99%
“…Apoptotic neutrophils cargo contributes to activation of macrophage NOX2 in a CD11b-TLR2/TLR4-myeloid differentiation primary response 88 (MyD88)-dependent manner and the subsequent ROS production, which is significantly delayed in macrophages from NOX2-deficient mice (46). While IgG-opsonized antigen cargo activates NOX2 dependent on FcγR-PKC/Syk pathway rather than V-ATPase (13,28,46).…”
Section: Ros and Macrophage Efferocytosismentioning
confidence: 99%